Dehydration: coupling centrifuge drainage with microwave drying operation - Apaolaza-Pagoaga, Xabier; Valat, Marc; Ginisty, Pascal; Jomaa, Wahbi; Sommier, Alain (Filtech, 2013)
In solid-liquid separation, the centrifugal drainage operation is an efficient and economic process for particulate suspensions which found main applications in the pharmaceutical, chemical and textile industries. It is often used before a thermal drying, and its interest relies on the elimination of most of the liquid at low energetic cost. Nevertheless, in many cases, the combination of mechanical and thermal operations in the same machine enables to optimize productivity, energy efficiency and safety aspects and to reduce cleaning fluids volumes and handling operations requirements. Microwave drying appears to be the most adapted technology to dry thick cakes in a centrifuge as basket rotation allows homogenizing electromagnetic fields leading to homogeneous heating. The heating is more efficient when the filtration cake is saturated but this process is expensive, so it is more interesting to mechanically dewater the cake and assist the process with microwave drying. Microwave heating should be brought in when mechanical dewatering sharply slows. The objective of this study is the optimization of coupling processes between mechanical dewatering and thermal drying by microwave. To reach this objective the development of a model with complete description of cake desaturation during centrifuge cycles is necessary, to implement thermal energy in order to assist the mechanical operation. To demonstrate the interest of the coupling process and the validity of the model, an instrumented pilot was developed and the first experiments were performed with model suspensions (talc, PVC) and industrial products (textile spool, Spath, etc.). Experimental results yielded to drainage curves during centrifuge cycle for these different products in various experimental conditions. The use of mathematical model allowed comparing experimental drainage curves with model predictions.
Keywords: Energía solar - Aplicaciones; New processes; Dewatering equipment; Mechanical thermal separation; Microwave; Drying; Energy efficiency